A Clinical Case of Aneurysmal Dilatation of the Aortic Arch Distal to the Origin of an Aberrant Right Subclavian Artery Treated with Castor Single-Branch Stent Graft Implantation and Right Carotid-Subclavian Bypass - Antonio Rizza; Silvia Di Sibio; Angela Buonpane; Giancarlo Trimarchi; Marta Casula; Michele Murzi; Pierandrea Farneti; Cataldo Palmieri; Marco Solinas; Sergio Berti (Journal of Cardiovascular Development and Disease)
Advancements in endovascular stent graft design have enabled the treatment of distal aortic arch pathologies. However, the length of the proximal landing zone remains a limitation, especially with vascular anomalies like an aberrant right subclavian artery (ARSA) posing additional challenges. A 78-year-old patient underwent computed tomography angiography (CTA), which revealed progressive enlargement of a distal aortic arch aneurysm located beyond an ARSA that coursed between the esophagus and trachea. Following evaluation by the multidisciplinary Aortic Team, a hybrid procedure was planned. A right carotid-to-ARSA bypass was performed and a Castor single-branched stent graft (CSBSG) was deployed in the aortic arch with its side branch directed into the left subclavian artery (LSA), thereby covering the origin of the ARSA. To prevent a type II endoleak, plug embolization of the ARSA origin was subsequently performed. CSBSG is a feasible treatment for distal aortic arch aneurysms, even in the presence of vascular anomalies such as ARSA.